Architectures and protocols that enable new applications on opticalnetworks. - Veeraraghavan, M. (IEEE Communications magazine)
This article first discusses how advances in networking architectures and protocols can complement advances in optical communications research to increase the overall value of optical networks by enabling more applications. A review of existing optical networking solutions is then provided along with a classification of different types of optical networks. Finally, we show how single-hop and multihop wavelength-routed networks can be used efficiently for fast end-to-end file transfers when these networks are equipped with a hardware-implementable signaling protocol, a routing protocol, and a simple transport protocol